The Influence of Purchase Interest on Purchasing Decisions Moderated by Word of Mouth: Study on Consumers of Sariayu Martha Tilaar Cosmetics in Ambon City - Nathania Tiatira Tableessy; Victor Ernest Huwae; Silfiena Siahainenia (ProBisnis : Jurnal Manajemen, 2023)
This research aims to examine and analyze the effect of purchase intention on purchasing decisions moderated by word of mouth for cosmetic consumers of Sariayu Martha Tilaar in Ambon City. The sampling method used a purposive sampling technique and data collection was carried out by distributing questionnaires which were distributed to 113 consumers. The analytical test tool used is SmartPLS 3 with the SEM (Structural Equation Modeling) analysis method. The results of this study indicate that buying interest has a positive and significant effect on purchasing decisions, and word of mouth moderates buying interest on purchasing decisions.